Quantification and correlation of anthocyanin pigments and their antioxidant activities in rose (Rosa hybrida) varieties - KUMARI, POONAM; RAJU, D V S; PRASAD, K V; SINGH, KANWAR PAL; SAHA, SUPRADIP; ARORA, AJAY; HOSSAIN, FIROZ (The Indian Journal of Agricultural Sciences, 2017)
The present study was conducted to evaluate the total anthocyanin content and their antioxidant activities in 50 Indian rose (Rosa hybrid L.) varieties. Total anthocyanin content among varieties was found maximum in December as compared to March. The total anthocyanin content differed significantly among all the varieties. The varieties with dark colours were richest in anthocyanin content than the light coloured varieties. A similar trend was also observed for antioxidant activity. The variety Ashwini, a dark red colour rose recorded highest anthocyanin content (578.10 mg/100g) followed by Dr S S Bhatnagar (369.86 mg/100g) and Nehru Centenary (288.15 mg/100g); whereas minimum anthocyanin content was recorded in white coloured varieties, i.e. Iceberg (0.24 mg/100g) followed by Mridula (0.53 mg/100g) and Shabnam (1.38 mg/100g). Among all the varieties tested, Ashwini recorded maximum antioxidant activity (512.71 Î¼mol Trolox/g), whereas least antioxidant activity was found in Iceberg (13.93 Î¼mol Trolox/g). The antioxidant capacity of all the varieties is correlated positively (R= 0.945) with their total anthocyanin content. This investigation will help to explore the possibilities of utilizing anthocyanin pigments from rose as potential nutraceutical, natural food colourant and also in breeding programmes for developing varieties with higher anthocyanin content. The findings also suggest that the dark colour can serve as an indicator of antioxidant activity.